2022
DOI: 10.3390/clockssleep4040042
|View full text |Cite
|
Sign up to set email alerts
|

STOP-Bang Score and Prediction of Severity of Obstructive Sleep Apnea in a First Nation Community in Saskatchewan, Canada

Abstract: The STOP-Bang questionnaire is an easy-to-administer scoring model to screen and identify patients at high risk of obstructive sleep apnea (OSA). However, its diagnostic utility has never been tested with First Nation peoples. The objective was to determine the predictive parameters and the utility of the STOP-Bang questionnaire as an OSA screening tool in a First Nation community in Saskatchewan. The baseline survey of the First Nations Sleep Health Project (FNSHP) was completed between 2018 and 2019. Of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Third, factors that may contribute to this difference include the accuracy of OSA measurement by sex. A recent Canadian study suggested that a STOP-BANG score of 5 or higher can accurately identify men with moderate-to-severe OSA, but it does not have diagnostic accuracy for identifying women with OSA [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, factors that may contribute to this difference include the accuracy of OSA measurement by sex. A recent Canadian study suggested that a STOP-BANG score of 5 or higher can accurately identify men with moderate-to-severe OSA, but it does not have diagnostic accuracy for identifying women with OSA [ 35 ].…”
Section: Discussionmentioning
confidence: 99%